REPRODUCTIVE PERFORMANCE OF BUFFALO IN SOUTH SULAWESI (A PRELIMINARY STUDY) - Abustam, Effendi; Yusuf, Muhammad; Toleng, Abdul Latief (Proceeding Buffalo International Conference, 2013)
This was a preliminary study that aimed to describe the reproductive performance of buffalo in South Sulawesi. The study was conducted in three different districts; Tana Toraja (R1), Enrekang (R2), and Wajo (R3). The number of buffalo involved in the present study was 147, 149, and 152 in R1, R2, and R3, respectively. Primary data were collected with the help of a questionnaire in interviewing the farmers and secondary data was obtained from livestock services in each region. The results of this study showed that the age at first buffalo heifers calved was >3.5 years; 91.9%, 71.9%, and 54.2% in R1, R2, and R3, respectively. The remaining buffalo heifers were calving â¤3.5 years of age. Days to first breeding after calving differed significantly (P<0.05) at different districts. In the region of R3 the number of buffalo bred within six months after calving was significantly (P<0.05) higher than in R2 and R1 (67.2% vs 38.0% and 56.6%). Furthermore, the number of buffalo first bred >12 months was significantly (P<0.05) higher in R2 in comparison to R1 and R3 (41.0% vs 20.9% and 19.5%). Moreover, calving interval within 18 months differed significantly (P<0.05) at different districts. In the region of R3, the number of buffalo with calving interval within 18 months was 56.3%; significantly (P<0.05) higher than in R1 and R2; 47.5% and 44.6%, respectively. In conclusion, reproductive performance of buffalo in South Sulawesi based on primary data collected from the farmers showed much better in the region of R3 in comparison to R1 and R2. Therefore, it is necessary to improve the reproductive performance in the two regions.